1998
DOI: 10.1073/pnas.95.26.15815
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 4,4′-diisothiocyanato-stilbene-2,2′-disulfonate on CO 2 permeability of the red blood cell membrane

Abstract: It has long been assumed that the red cell membrane is highly permeable to gases because the molecules of gases are small, uncharged, and soluble in lipids, such as those of a bilayer. as expected, but also appeared to reduce intracellular A, although separate experiments showed it has no effect on CA activity in homogenous solution. A decrease in P m,CO 2 would explain this finding. With a more advanced computational model, which solves for CA activity and membrane permeabilities to both CO 2 and HCO 3 ؊ , we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
71
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 18 publications
9
71
1
Order By: Relevance
“…However, our results do not prove that CO 2 transport in erythrocytes is not unstirred layerlimited. It has been debated whether CO 2 movement across erythrocytes is unstirred layer-limited, but more recent studies suggest that the membrane constitutes the rate-limiting barrier (34). We note that the conclusions of our study regarding the physiological role of AQP1 in erythrocyte CO 2 permeability do not depend upon identification of the rate-limiting barrier for CO 2 transport across erythrocyte membranes.…”
Section: Discussionsupporting
confidence: 50%
“…However, our results do not prove that CO 2 transport in erythrocytes is not unstirred layerlimited. It has been debated whether CO 2 movement across erythrocytes is unstirred layer-limited, but more recent studies suggest that the membrane constitutes the rate-limiting barrier (34). We note that the conclusions of our study regarding the physiological role of AQP1 in erythrocyte CO 2 permeability do not depend upon identification of the rate-limiting barrier for CO 2 transport across erythrocyte membranes.…”
Section: Discussionsupporting
confidence: 50%
“…Indeed, Forster et al (54) first detected such a CO 2 transport activity in addition to band 3 across the membrane of intact human red cells. Notably, the Cl Ϫ ͞HCO 3 Ϫ exchange mechanism operates in teleost fish but not jawless fish, because zebrafish has a genuine band 3 (55), whereas the red cell membrane of hagfish is impermeable to HCO 3 Ϫ (56).…”
Section: Discussionmentioning
confidence: 99%
“…The diffusion coefficient for a dilute solution of CO 2 in water at 20°C is 1.78 ϫ 10 Ϫ9 ⅐ m 2 ⅐ s Ϫ1 (22), and this provides the principal constraint on the overall diffusion rate, unless cell boundary structures provide a significant extra barrier. No direct measurements of the diffusivity of molecular CO 2 across the cell boundary of E. coli cells appear to have been made, but in the case of red blood cells the most recent and sensitive measurements (14) have shown that the cell membrane provides only a small additional diffusive barrier. Diffusion equations (4) can be combined with the aqueous diffusion coefficient and the shape and size of a typical E. coli cell (19) to estimate that if the net rate of production of CO 2 in a cell is F mol ⅐ s Ϫ1 , the excess steady-state concentration (above the equilibrium concentration corresponding to the gas phase composition) will be about F ϫ 10 11 mol ⅐ liter Ϫ1 .…”
Section: Discussionmentioning
confidence: 99%